Factores de riesgo biológicos en recicladores informales de la ciudad de Medellín, 2005 (2008)
ABSTRACT: The informal recyclers constitute a vulnerable population to problems of health by their constant exhibition to biological, chemical, physical and social risks, without protection. Objective: this work identify the biological risk facts to which the informal recyclers of the Bazaar of the Bridges of Medellin city. Methods: it was performed a Cross-sectional study. The sample was no probabilistic with 88 recyclers and the analysis unit was the informal recycler. It was applied a survey, a guide of observation of the activity of the recycler and were studied variables of person, place, time, type of biological risk facts, frequency of exhibition, felt morbidity and measures of protection. The analysis was statistical descriptive. Results: it was identified biological risk facts related to the contact with material in decomposition (96.6%), contaminated material (96.6%), animals (62.5%) and arthropoda (79.5%). The se - curity measures to protect them from biological risk facts are used in less than 52% of recyclers; in addition, only 13.6% of the population were vaccinated, which increases the probability of becoming ill in this population. Conclusions: that the informal recyclers are exposed to different biological risk facts with little prevention, causing that population be vulnerable for the acquisition of infectious diseases.